Albedo enhancement by stratospheric sulfur injections: More research needed. Issue 12 (18th December 2016) - Robock, Alan
Abstract: Research on albedo enhancement by stratospheric sulfur injection inspired by Paul Crutzen's paper a decade ago has made clear that it may present serious risks and concerns as well as benefits if used to address the global warming problem. While volcanic eruptions were suggested as innocuous examples of stratospheric aerosols cooling the planet, the volcano analog also argues against stratospheric geoengineering because of ozone depletion and regional hydrologic responses. Continuous injection of SO2 into the lower stratosphere would reduce global warming and some of its negative impacts, and would increasing the uptake of CO2 by plants, but research in the past decade has pointed out a number of potential negative impacts of stratospheric geoengineering. More research is needed to better quantify the potential benefits and risks so that if society is tempted to implement geoengineering in the future it will be able to make an informed decision. Key Points: Paul Crutzen warned the world about dangerous global warming and inspired important geoengineering research in 2006 Stratospheric geoengineering could present a number of risks and concerns as well as benefits, but there are still many issues to address More research on geoengineering is needed so that if society is tempted to implement geoengineering, it will be an informed decision